Artificial Intelligence, Posthumanism, and New Directions of Humanities Education - Ferdinandus - Jehalut; Fransiskus Bala Kleden; Frederik Masri Gasa (Jurnal Ledalero, 2025)
Humanism-Renaissance established humans as the center and measure of everything. This view is now being deconstructed amid the rapid development of artificial intelligence (AI) technology, which has the capacity to ‘think’, innovate, and act (make decisions). According to Rosi Braidotti, this situation marks the emergence of a new era in thought, namely the posthuman era. This article aims to explain the key theses of posthumanism. Specifically, this article seeks to explore the implications of the posthumanist perspective on humanities education. This qualitative study uses secondary data analysis methods. The research finds that posthumanism is characterized by the decentralization of humans and the blurring of boundaries between humans and non-human entities. This has implications for the deconstruction of traditional benchmarks in humanities education, which are based on values and principles of rationality, empathy, creativity, and morality. Humanities education in the post-human era must be designed not only to explore these values and principles but also to understand the dynamic interactions between humans, technology, and nature. The design of humanities education in the post-human era needs to adopt a transdisciplinary and interdisciplinary approach that integrates ethical understanding and responsibility in the context of human-technology interaction.